QS7: Physiologic Signaling of the Muscle Cuff Regenerative Peripheral Nerve Interface (MC-RPNI) During Volitional Behavior. (July 2021) - Svientek, Shelby R.; Bratley, Jarred; Dehdashtian, Amir; Kubiak, Carrie; Cederna, Paul; Kemp, Stephen
Abstract : Purpose: Exoskeletons have become a promising device to restore extremity function to those with limb weakness. However, these devices have not become widely adopted due to the inadequacy of current nerve interfacing methods. The Muscle Cuff Regenerative Peripheral Nerve Interface (MC-RPNI) was developed as a potential solution to this problem. Consisting of a segment of autologous free muscle secured around an intact nerve, the MC-RPNI is able to regenerate and reinnervate, amplifying its contained nerve's signals through generation of EMG signals. These amplified, high-fidelity signals can then be used to intuitively and accurately control exoskeletons. The purpose of this study was to characterize MC-RPNI physiologic signaling during volitional behavior and determine long-term effects on the associated nerve. Methods: Eighteen rats were randomly assigned to one of three groups: (1) sham surgery/control; (2) nerve transection; and (3) MC-RPNI. MC-RPNIs were surgically fabricated by wrapping isogenic donor muscle graft circumferentially around the common peroneal (CP) nerve. At six months, CP nerve cuff electrodes were implanted in Groups 1 and 2, and patch electrodes were placed on all MC-RPNIs. Gait analysis and electrophysiological evaluations were performed the following day. Rats were trained to walk on a treadmill, and electrode recordings were obtained and correlated with gait videocapture. All rats had their proximal CP nerve stimulated, with efferent signals obtained at (1) downstream nerve (CSNAP), (2) MC-RPNI (CMAP), and (3) downstream-innervated extensor digitorum longus (EDL) muscle (CMAP). EDL muscle force testing was also performed following stimulation of the CP nerve. Results: All MC-RPNIs remained viable and demonstrated appropriate regeneration, revascularization, and reinnervation on histology. The MC-RPNI was found to generate large-amplitude CMAPs (2.77+/-0.926mV), amplifying its associated nerve's signal (50.5+/-8.18µV) over 50-fold on average. The MC-RPNI was not found to affect muscle function when evaluating downstream-innervated EDL CMAPs (control: 13.4+/-2.33mV vs MC-RPNI: 14.1+/-1.44mV) or maximal twitch force (control: 562+/-70.8mN vs MC-RPNI: 653+/-34.6mN). On gait analysis, recordings from the MC-RPNI correlated with the toe-off phase of gait; for the control groups, nerve signaling could not be differentiated from background noise. When comparing MC-RPNI to control animal gait, no significant differences were noted on qualitative or joint-angle analysis. Conclusion: The MC-RPNI has the ability to chronically amplify physiologic nerve signals from intact peripheral nerves by several magnitudes while avoiding functional impairment of downstream-innervated muscle. This amplification has the capability to facilitate high accuracy detection of motor intent in order to intuitively and reliably control advanced exoskeleton devices.